Finding high-redshift voids using Lyman α forest tomography. Issue 4 (16th September 2015) - Stark, Casey W.; Font-Ribera, Andreu; White, Martin; Lee, Khee-Gan
Abstract: We present a new method of finding cosmic voids using tomographic maps of Lyα forest flux. We identify cosmological voids with radii of 2–12  h −1  Mpc in a large N -body simulation at z  = 2.5, and characterize the signal of the high-redshift voids in density and Lyα forest flux. The void properties are similar to what has been found at lower redshifts, but they are smaller and have steeper radial density profiles. Similarly to what has been found for low-redshift voids, the radial velocity profiles have little scatter and agree very well with the linear theory prediction. We run the same void finder on an ideal Lyα flux field and tomographic reconstructions at various spatial samplings. We compare the tomographic map void catalogues to the density void catalogue and find good agreement even with modest-sized voids ( r  > 6  h −1  Mpc). Using our simple void-finding method, the configuration of the ongoing COSMOS Lyman Alpha Mapping And Tomography Observations (CLAMATO) survey covering 1 deg 2 would provide a sample of about 100 high-redshift voids. We also provide void-finding forecasts for larger area surveys, and discuss how these void samples can be used to test modified gravity models, study high-redshift void galaxies, and to make an Alcock–Paczynski measurement. To aid future work in this area, we provide public access to our simulation products, catalogues, and sample tomographic flux maps.